High Propagule Pressure and Patchy Biotic Resistance Control the Local Invasion Process of the Tree Ligustrum lucidum in a Subtropical Forest of Uruguay - Alejandro Brazeiro; Federico Haretche; Carolina Toranza; Alexandra Cravino (Plants)
The tree Ligustrum lucidum (W. T. Aiton, Oleaceae), native to East Asia (China), has become an aggressive invader of subtropical and temperate forests around the world. To understand how its local small-scale spread is controlled, we studied (48 plots of 4 m−2), in a subtropical forest of Uruguay, the distribution and survival of seedlings, saplings, and poles to assess the effects of dispersal from mother trees (distance), microsite type (forest stands defined by dominant species), and past control measures. The propagule pressure of L. lucidum, estimated through seedlings density, was between 100 and 1000 times higher than that of other species of the community and was concentrated around mother trees (<10 m of distance). Spatial variability of seedlings, saplings, and poles densities were explained by the interaction between distance to mother trees and forest stands. Significative lower densities were observed in the forest patches (stands) dominated by Jodina rhombifolia, and a field survival experiment confirmed lower survival of poles at Jodina stands, demonstrating that some resistance mechanism is operating there. We propose two biotic mechanisms of resistance: herbaceous competition and/or roots hemiparasitism by J. rhombifolia, reducing seedling and sapling survival. We concluded that a high propagule pressure, small-scale dispersal from mother trees, and patchy biotic resistance at Jodina stands control the local spread and domination process of the tree L. lucidum in the studied forest.